Penguatan Literasi, Numerasi dan Adaptasi Teknologi di SDN 019 Tanjung Selor Melalui Program Kampus Mengajar Angkatan 5 - Barumbun, Mardyanto; Palebangan, Clara Septiani; Wahyuni; Moron, Maria Ketane; Kojongian, Heny; Royani, Luthfi Maulida (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Kampus Mengajar as a government program aimed at students to conduct off-campus learning for one semester aims to improve the literacy and numeracy of students in Indonesia which is still very lacking. SD Negeri 019 Tanjung Selor, North Kalimantan is one of the partners in the implementation of the 5th Batch Teaching Campus, with the main objective of this service program in the form of assistance for teachers and students in learning activities, especially literacy and numeracy, assistance in adapting educational technology for teachers and students, and administrative assistance for schools in addition to implementing other additional work programs. The implementation of this community service uses the Participatory Action Research (PAR) method, which requires active participation from related parties to analyze the activities being carried out. This program is carried out for 5 months consisting of debriefing, implementation, and reporting activities. The results of this service program show that the implementation of the Teaching Campus program increases student literacy and numeracy, provides additional skills for teachers and students in the use of technology at SD Negeri 019 Tanjung Selor, and develops the potential of student participants outside the campus.